HUBUNGAN ANTARA PARITAS IBU BERSALIN DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH DI RSUD CILACAP TAHUN 2009 - Aida Fitria; Lindayanti Lindayanti (Viva Medika, 2009)
In Indonesia the low Birth Weight Infants (LBW) is one of the factors the causes of infant mortality. In 2008 in Central Java province percentage of LowBirth Weight and 2,08%, preliminary survey that has been conducted at thePROVINCIAL HOSPITAL in 2009, Cilacap case LBW reached 18% of the totalnumber of births. The purpose of this research is to know the relationship betweenthe parity of birthing mothers with babies of low birth weight incidence in CilacapHOSPITALS in 2009. The methods used in this research is descriptive analyticapproach with retrospective study, sampling using the technique of total samplingnamely whole mothers who gave birth in Hospitals Cilacap in 2009 IE as much as1391 respondents, this study uses secondary data taken with medical record entrylook back mother who gave birth to Low Birth Weight babies in Hospitals Cilacapin 2009. The research results obtained by the incidence of Low Birth Weight mostoccur on parity parity Group 1 and 2-4, based on the analysis of the obtainedresults Ñ… Â² count (0.019) < Ñ… Â² table (5.991) and p value (0.991) > 0.005 there isno relationship between the parity of birthing mothers with babies of low birthweight incidence in Cilacap HOSPITALS in 2009. The conclusions of the studyresults it can be concluded that there is no relationship between the parity ofbirthing mothers with Low Birth Weight in Cilacap Hospitals in 2009. Key words: maternal Parity in labor, Low Birth Weight